2019
DOI: 10.3389/fneur.2019.00417
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Thrombolysis in Posterior Circulation Stroke

Abstract: Background: Intravenous thrombolysis (IVT) is a standard treatment for both anterior circulation ischemic stroke (ACIS) and posterior circulation ischemic stroke (PCIS). PCIS is a clinical syndrome associated with ischemia-related changes in the territory of the posterior circulation arteries. Embolism is the most common stroke mechanism in posterior circulation. PCIS represents 12–19% of all IVT-treated strokes. Methods and Results: We searched the PubMed database for assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 61 publications
4
27
0
3
Order By: Relevance
“…Although we recorded 7 cases with mRS 6 among ACS group compared to none among PCS group, but this difference was non-significant (p value 0.61) which is found to be in line with other studies that reported lower mortality rate among PCS compared to ACS with lack of significant difference [13,14].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although we recorded 7 cases with mRS 6 among ACS group compared to none among PCS group, but this difference was non-significant (p value 0.61) which is found to be in line with other studies that reported lower mortality rate among PCS compared to ACS with lack of significant difference [13,14].…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, the functional outcome of the cases at discharge and 90 days was found to be better in PCS compared to ACS; 75.17% and 93.75% in PCS had mRS ≤2 in comparison to ACS that showed only 59.24% and 70% of the cases with mRS ≤2 respectively; this agrees with a systematic review performed on other retrospective published studies comparing the efficacy of IVT [12], but disagrees with another prospective cohort study that mentioned that despite mRS was lower in the posterior circulation, there was no significant difference between the two groups; this contradictory could be due to the limited sample size in the mentioned study [13] as they recruited only 30 posterior circulation and 198 anterior circulation.…”
Section: Discussionsupporting
confidence: 47%
“…For ACS, knowledge on symptom onset may have outweighed the influence of the OTT on the mRS in multivariate regression analysis. For PCS, the OTT has been shown to be less crucial in thrombolysis 35 which might explain the lack of influence of known symptom onset and OTT on functional outcome in PCS patients.…”
Section: Discussionmentioning
confidence: 99%
“…In scenarios with A2/3 occlusion, immediate EVT was favored only by 51% (alteplase-eligible patients)/71% (alteplaseineligible patients) of respondents, while these numbers were much higher for scenarios with M2/3 occlusion (57%/83%) and P2/3 occlusion (82/67%). The relatively high willingness to proceed with immediate EVT in P2/3 MeVOs could potentially reflect the lack of high-level evidence for IV thrombolysis in posterior circulation MeVOs, 19 though one could argue that this applies to EVT as well. In fact, the safety and efficacy of EVT has not even been formally proven for LVOs in the posterior circulation, 20 and there is complete paucity of high-level evidence on EVT for MeVOs in posterior circulation.…”
Section: Ischemic Strokementioning
confidence: 99%